Mining the genome. - Applewhite, A. (IEEE spectrum)
Having tackled the human genome, Celera's Gene Myers is now advancing on proteins and drug development. This article discusses Myers' work on developing computational biology for the human genome project. The further development of computational biology for the pharmaceutical industry is also discussed